Diagnóstico de la organización del trabajo en las unidades de docencia, investigación y vinculación de la carrera Agroindustria - ESPAM MFL - Karina Fernanda, Mero Triviño (2014)
The objective of this study was to diagnose the factors that have an impact on the organization of work that contributes to the proposal for a programme of improvements to ensure the quality of working life of the employees of the career of agribusiness of the ESPAM MFL, for this purpose was designed and applied a procedure allowing the familiarization with the area through an interview applied to workers of teaching units in its first stagere search and career above, linking consecutively evaluated the organization's work through a general assessment questionnaire and another specific to the study of the system of work and rest using time study technique which admitted to collect information from the structure of the workday; in addition the bimanual diagram technique was used for the methods of work (left and right hand movements) in production processes. In terms of results obtained flaws as continuous activities, were without health teams for greater inconvenience, not provided all protection kitchenware, fatigue or stress, lack of technological capability and routine operations, all these were prioritised using the Kendall method to represent them in a diagram cause effect and recognize the sub-causes who taxed them. The above led to develop a programme of improvements with corrective and preventive actions using your application that allowed to guarantee the quality of life of the workers, the occupational health and safety.